Trade credit in China: Exploring the link between short term debt and payables - Tang, Ying; Moro, Andrea (Elsevier, 2019)
Trade credit constitutes an essential element of short-term financing for most firms, especially for small and medium-sized enterprises. This paper investigates the dynamics between short-term bank debt and payables among 1525 Chinese small and medium-sized listed companies over the period of 2008–2016. The results suggest that an increase in stock and receivables is financed by both bank credit and payables. In addition, we find that bank credit and payables substitute each other. We also uncover a strong substitution effect among weak firms, possibly linked to the fact that weak firms struggle to access additional bank finance and thus are forced to rely on suppliers to support their growth. The substitution effect between payables and bank credit is robust to different cash conversion cycles and to the firm's liquidity.
Keywords: Trade credit; Short-term debt; Payables; SME